О КАЧЕСТВЕ БИБЛИОТЕЧНОГО ОБЩЕНИЯ - S. A. Jezova (Библиосфера)
The approach to the quality of library contacts from the viewpoint of the conception of personality relations (V. N. Mjasischev) and theory of activity (V. D. Nebylitsyn) is shown. Foreign theories of interpersonal relations.